Global norms and heterogeneous development organizations: Introduction to special issue on New Actors, Old Donors and Gender Equality Norms in International Development Cooperation. (April 2018) - Cold-Ravnkilde, Signe Marie; Engberg-Pedersen, Lars; Fejerskov, Adam Moe
Contemporary development cooperation is characterized by an increasing tension between a growing diversity of actors and significant attempts at homogenizing development practices through global norms prescribing 'good development'. This special issue shows empirically how diverse development organizations engage with global norms on gender equality. To understand this diversity of norm-engagement conceptually, this introductory article proposes four explanatory dimensions: (i) organizational history, culture and structures; (ii) actor strategies, emotions and relationships; (iii) organizational pressures and priorities; and (iv) the normativeenvironment and stakeholders. We argue that, while development organizations cannot avoid addressing global norms regarding gender equality, they do so in considerably divergent ways. However, the differences are explained less by whether these organizations constitute 'new' or 'old' donors than by the four identified dimensions.